Webinar - Case Studies of Bundled Innovations for Women's Empowerment and Resilience- January 2024 - CGIAR Gender Equality initiative (CGIAR GENDER Impact Platform, 2024)
CGIAR Initiative on Gender Equality, Work Package ‘EMPOWER’ led by International Rice Research Institute (IRRI), with funding support from the CGIAR Gender Impact Platform, documented cases from different parts of India where social, technical, and technological innovations are bundled for enhancing women's empowerment and resilience. In this webinar, held on 25th January, 2024, speakers from partner organizations highlighted the key highlights of their findings.